Analysis of the Effect of Legendary Taste on Buying Interest at Purnama Coffee Shop, Bandung City - Teduh Primandaru (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
A taste is one of the key elements in attracting and improving buying interest of a coffee shop. More over if the taste is perceived as legendary. Purnama coffee shop, which is located in the heart of municipality of Bandung has this added value in perceiving a legendary taste of their menus. Is it true taste that is perceived legendary directly correlated to the improvement of buying interest? This research is aimed to know and analyze the effect of taste that is perceived legendary in improving the buying interest at Purnama Restaurant, in Bandung. This research uses multiple regression analysis by applying SPSS 24.0. This is a descriptive explanatory research form. The result of this research shows that the taste variable has a positive and significant effect toward the variable of buying interest of a coffee shop.